The Effect of Organic Liquid Fertilizer Chicken Eggshell with Onion Skin Waste For The Growth and Yield of Basil Plant (Ocimum basilium L.): Pengaruh Pemberian Pupuk Organik Cair (POC) Limbah Cangkang Telur Ayam dan Kulit Bawang Merah Terhadap Pertumbuhan dan Hasil Tanaman Kemangi (Ocimun basilicum L.) - Waliyuddin, Achmad Wirdan (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of applying liquid organic fertilizer from chicken eggshell and onion skin waste for the growth and yield of Basil plants which were carried out from May to June 2023, using a single factor Randomized Block Design (RBD) with 4 experimental levels, namely D0: Without POC, D1: (100 ml POC + 1 L Water), D2: (200 ml POC + 1 L Water), D3: (300 ml POC + 1 L Water), D4: (400 ml POC + 1 L Water ) which was repeated 3 times. The variables observed were plant height, number of leaves, number of branches, stem diameter, flower weight, leaf weight and plant weight. Then analyzed the variance using ANOVA to determine the effect of giving POC which will then be carried out by a BNJ follow-up test. The results of the study showed that the application of liquid organic fertilizer from chicken eggshell and onion skin waste in D2 treatment with a dose of 200 ml POC + 1 L of water gave the highest yields of basil plants with the highest number of leaves, number of branches and leaf weight.